2016
DOI: 10.1051/matecconf/20164704005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Outdoor Thermal Comfort and Wind Characteristics at Three Different Locations in Peninsular Malaysia

Abstract: Abstract. Urbanization and rapid growth in construction have led to the problems of global warming and urban heat island throughout the world. In order to reduce these problems particularly in hot and humid climatic region, a research on current level of outdoor thermal comfort and wind characteristics based on the local weather conditions around Malaysia should be conducted. This paper reports on the analysis of outdoor thermal comfort level at hottest temperatures and wind characteristics at three locations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Malaysia has generally been identified as a low-wind, hot and humid country, with available data describing the mean wind speed as below the level recommended for thermal comfort, unsuitable for driving natural ventilation at the indoor space 24) . For example, Hanipa et al 25) put the mean wind speed around the capital city of Kuala Lumpur to range from 1.63 m/s to 1.7 m/s; Wen et al 26) stated the mean velocity in Malaysia to be between 2 m/s and 3 m/s; and Ayo et al 27) reported the mean wind speed around Kuala Lumpur as 1.52 m/s. Observed that these wind speeds are normally measured around open terrains far from the built-up areas and at 10 m meteorological height above the ground level 26) which would be much lower at the pedestrian-level height of between 1.5 m and 2 m, the mean wind speed in Malaysia, particularly around the Capital City of Kuala Lumpur, is below that necessary for thermal comfort at the indoor space suggested to range between 0.1 m/s and 1.5 m/s 28) .…”
Section: Methodology Of the Research 21 Physical Modelling And Config...mentioning
confidence: 99%
“…Malaysia has generally been identified as a low-wind, hot and humid country, with available data describing the mean wind speed as below the level recommended for thermal comfort, unsuitable for driving natural ventilation at the indoor space 24) . For example, Hanipa et al 25) put the mean wind speed around the capital city of Kuala Lumpur to range from 1.63 m/s to 1.7 m/s; Wen et al 26) stated the mean velocity in Malaysia to be between 2 m/s and 3 m/s; and Ayo et al 27) reported the mean wind speed around Kuala Lumpur as 1.52 m/s. Observed that these wind speeds are normally measured around open terrains far from the built-up areas and at 10 m meteorological height above the ground level 26) which would be much lower at the pedestrian-level height of between 1.5 m and 2 m, the mean wind speed in Malaysia, particularly around the Capital City of Kuala Lumpur, is below that necessary for thermal comfort at the indoor space suggested to range between 0.1 m/s and 1.5 m/s 28) .…”
Section: Methodology Of the Research 21 Physical Modelling And Config...mentioning
confidence: 99%
“…Testing was performed in a closed-loop wind tunnel in the Wind Tunnel Laboratory at the Science and Engineering Research Centre of Universiti Sains Malaysia using a a smoke generator at airflow speeds of 0.5 m/s, 1.0 m/s, 2.0 m/s, 3.0 m/s and 5.0 m/s, with ventilation rates of 0.103 m 3 /s, 0.205 m 3 /s, 0.410 m 3 /s, 0.616 m 3 /s and 1.026 m 3 /s, respectively. The speeds were chosen because they represented the range of average wind speeds in the hot and humid climate of Malaysia (Lim et al, 2011;Makaremi et al, 2012;Bakar & Gadi, 2016;Hanipah et al, 2016;Hanipah et al, 2017). Smoke was used to evaluate airflow characteristics of the wooden slotted down window panel model.…”
Section: Smoke Flow Visualisation Technique (Ie Smoke Generator Technique)mentioning
confidence: 99%
“…The UHI effect is a type of urban thermal pollution that happens due to higher ambient air temperatures in densely-built environments compared to their rural peripheries [6][7][8][9][10][11][12][13][14]. Consequently, urban dwellers are prone to higher and longer levels of heat exposure, which cause the deterioration of outdoor thermal comfort (OTC) levels [15][16][17][18][19] and impact their well-being [20]. A constant rise in temperature will also lead to the aggravation of heat-related illnesses and mortalities [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%